Controllable synthesis method of ni-n-c material and application thereof

CN117488347BActive Publication Date: 2026-10-27HUBEI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311345290.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2026-10-27
Estimated Expiration
2043-10-16

AI Technical Summary

Technical Problem

[0005]但是现有技术在合成催化剂并电解一氧化碳的过程中,其合成氧化时间的不同都难以调控到合成气比例的变化,使得难以控制合成催化剂并电解一氧化碳的效率,因此我们提出了一种Ni-N-C材料的可控合成方法及其应用

Benefits of technology

[0022]本发明的有益效果是:该催化剂易于制备,控制不同氧化时间即可制备不同表面修饰的镍单原子包覆的镍纳米簇的催化剂,根据氧化时间的不同能够宽范围调控合成气比例的变化。该催化剂的稳定性很好,经过长时间电解后,其还原CO2至CO和H2混合气的电流效率也无明显衰减。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117488347B_ABST
    Figure CN117488347B_ABST
Patent Text Reader

Abstract

The application discloses a controllable synthesis method of a Ni-N-C material and application thereof, and comprises the following steps: step one, preparing a solution and synthesizing a black solid; step two, preparing a Ni-N-C catalyst; and step three, preparing a working electrode.The Ni-N-C catalyst is easy to prepare, and different surface modified nickel nanocluster catalysts coated with nickel monatomic atoms can be prepared by controlling different oxidation times, and the change of syngas proportion can be controlled in a wide range according to different oxidation times.The stability of the catalyst is very good, and the current efficiency of the catalyst for reducing CO2 into CO and H2 mixed gas is not obviously attenuated after long-time electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a controllable synthesis method, specifically a controllable synthesis method for Ni-NC materials and its application, belonging to the field of Ni-NC material technology. Background Technology

[0002] CO2 conversion and utilization are of great significance for mitigating the global environmental crisis and contributing to the global goal of "carbon peaking and carbon neutrality." Therefore, there is an urgent need to develop advanced CO2 conversion and utilization technologies to address the current CO2 problem. In this regard, many emerging technologies, such as chemical fixation and electro / photochemical reduction, have been proposed to suppress carbon dioxide release.

[0003] Among these technologies, electrochemical carbon dioxide reduction reaction (CO2RR) is considered a potential pathway to produce value-added chemicals and fuels when combined with renewable energy. Electrocatalytic reduction of CO2 directly converts it into other usable renewable energy sources, which is significant for both reducing greenhouse gas CO2 emissions and producing high-value-added chemicals to alleviate the energy crisis. Moreover, due to its advantages such as wide and stable power sources, simple structure, mild reaction, and high reaction efficiency, electrocatalytic reduction technology has become one of the hot topics in the field of energy storage and conversion in recent years, attracting the attention and research of many researchers.

[0004] Among the potential products, carbon monoxide production is a method of great interest because carbon monoxide can be readily used as a feedstock for value-added chemicals and fuels through existing thermochemical reactions. For these reasons, gold (Au), silver (Ag), zinc (Zn), and palladium (Pd) have been extensively studied for CO production. Syngas (CO, H2) is an important chemical feedstock and a crucial component of C1 chemistry. The efficient conversion of syngas into clean liquid fuels and high-value-added chemicals, along with the diverse range of syngas chemical products, are indispensable feedstocks for the chemical and other industries, offering greater possibilities for effectively alleviating ecological pressure.

[0005] However, in the process of synthesizing catalysts and electrolyzing carbon monoxide, the existing technology makes it difficult to control the change in the synthesis gas ratio by varying the synthesis oxidation time, which makes it difficult to control the efficiency of synthesizing catalysts and electrolyzing carbon monoxide. Therefore, we propose a controllable synthesis method for Ni-NC materials and its application. Summary of the Invention

[0006] The purpose of this invention is to provide a controllable synthesis method for Ni-NC materials and its applications to solve the aforementioned problems. Catalysts with nickel nanoclusters coated with nickel single atoms and modified with different surface finishes can be prepared by controlling different oxidation times. The syngas ratio can be adjusted over a wide range according to the oxidation time. Even after prolonged electrolysis, the current efficiency for reducing CO2 to a mixture of CO and H2 shows no significant decrease.

[0007] This invention achieves the above objective through the following technical solution: a controllable synthesis method for Ni-NC materials and its application, comprising the following steps:

[0008] Step 1: Prepare the solution and synthesize the black solid;

[0009] First, prepare the Ni-NC precursor solution by adding 3.5 mmol of ZnCl2 powder and 0.1 mmol of Ni(NO3)2 solid to 30 ml of formamide solution and stirring to dissolve. Transfer the solution to a 50 ml Teflon-lined stainless steel autoclave and seal it immediately. Keep it in an oven at 180 °C for 12 hours. After naturally cooling to room temperature, wash the obtained solution several times with deionized water and anhydrous ethanol, filter it, and dry it overnight at 60 °C to obtain a black solid.

[0010] Step 2: Preparation of Ni-NC catalyst;

[0011] Ni-NC particles were obtained by calcining a black solid in an argon atmosphere at 850–950 °C for 2 h; the previously treated Ni-NC particles were then calcined in an air atmosphere at 250–350 °C. The ratio of Ni-NC to nickel nanoclusters was controlled to prepare a Ni-NC catalyst with nickel nanoclusters coated with nickel single atoms.

[0012] Step 3: Prepare the working electrode;

[0013] In an H-type electrolytic cell divided into an anode and cathode compartment by a Nafion 117 proton exchange membrane (PEM), a platinum sheet and Ag / AgCl (3.5M saturated KCl solution) were used as the counter electrode and reference electrode, respectively. The electrode dimensions were 1.0 × 1.0 cm. 2 Carbon paper coated with a catalyst was used as the working electrode. 60 ml of 0.1 M KHCO3 solution was placed in the electrolytic cell. Before the test, CO2 was continuously injected into the electrolyte at a rate of 20 ml / min for at least half an hour until saturation. Then, CO2 was reduced at a constant potential under continuous CO2 supply. Electrolysis was carried out at different constant potentials, and the composition of the products at each specific potential was determined.

[0014] The potential control during the constant potential reduction process is -1.3V to -1.8V. When preparing the working electrode, 5mg of catalyst is dispersed in 980μL of anhydrous ethanol, and then 20μL of Nafion 117 solution is added. The mixture is sonicated for 40min to form a uniform ink. 200μL of the ink is then dropped onto carbon paper and dried under an infrared lamp for use.

[0015] Preferably, the Ni-NC particles are calcined in an air atmosphere at 250-350°C for 0 hours, i.e., they are not calcined.

[0016] Preferably, the Ni-NC particles are calcined in an air atmosphere at 250–350°C for 1 hour.

[0017] Preferably, the Ni-NC particles are calcined in an air atmosphere at 250–350°C for 3 hours.

[0018] Preferably, the Ni-NC particles are calcined in an air atmosphere at 250–350°C for 6 hours.

[0019] Preferably, the Ni-NC particles are calcined in an air atmosphere at 250–350°C for 9 hours.

[0020] Preferably, the Ni-NC particles are calcined in an air atmosphere at 250–350°C for 12 hours.

[0021] An application of Ni-NC material, including a system application that modulates the change in syngas ratio with increasing Ni-NC oxidation time.

[0022] The beneficial effects of this invention are: the catalyst is easy to prepare, and catalysts with nickel nanoclusters coated with nickel single atoms and modified with different surface finishes can be prepared by controlling different oxidation times. The syngas ratio can be adjusted over a wide range according to different oxidation times. The catalyst has excellent stability; even after long-term electrolysis, its current efficiency in reducing CO2 to a mixture of CO and H2 does not show significant attenuation. Attached Figure Description

[0023] Figure 1 The results are X-ray diffraction analysis of the surface of the Ni-NC catalyst of this invention at different oxidation times.

[0024] Figure 2 The results are obtained by scanning electron microscopy analysis of the surface of Ni-NC catalyst at different oxidation times (0h, 1h, 3h, 6h, 9h, 12h).

[0025] Figure 3 The present invention is Ni-NC@Ni NCs(3h) Transmission electron microscopy analysis results of the surface.

[0026] Figure 4 The linear sweep voltammetry (LSV) tests were performed on six samples of Ni-NC catalyst oxidized for different times in this invention.

[0027] Figure 5 This is a Faraday efficiency diagram of CO2 reduction to CO at different potentials after Ni-NC oxidation for different times according to the present invention.

[0028] Figure 6 This is a graph showing the change in current density over time during the electrocatalytic reduction of CO2 to CO by the catalyst after Ni-NC oxidation for 3 hours under a constant potential of -1.6V. Detailed Implementation

[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] This invention discloses a controllable synthesis method for Ni-NC materials.

[0031] Includes the following steps:

[0032] Step 1: Prepare the solution and synthesize the black solid;

[0033] First, prepare the Ni-NC precursor solution by adding 3.5 mmol of ZnCl2 powder and 0.1 mmol of Ni(NO3)2 solid to 30 ml of formamide solution and stirring to dissolve. Transfer the solution to a 50 ml Teflon-lined stainless steel autoclave and seal it immediately. Keep it in an oven at 180 °C for 12 hours. After naturally cooling to room temperature, wash the obtained solution several times with deionized water and anhydrous ethanol, filter it, and dry it overnight at 60 °C to obtain a black solid.

[0034] Step 2: Preparation of Ni-NC catalyst;

[0035] Ni-NC particles were obtained by calcining a black solid in an argon atmosphere at 850–950 °C for 2 h; the previously treated Ni-NC particles were then calcined in an air atmosphere at 250–350 °C. The ratio of Ni-NC to nickel nanoclusters was controlled to prepare a Ni-NC catalyst with nickel nanoclusters coated with nickel single atoms.

[0036] Step 3: Prepare the working electrode;

[0037] In an H-type electrolytic cell divided into an anode and cathode compartment by a Nafion 117 proton exchange membrane (PEM), a platinum sheet and Ag / AgCl (3.5M saturated KCl solution) were used as the counter electrode and reference electrode, respectively. The electrode dimensions were 1.0 × 1.0 cm. 2 Carbon paper coated with a catalyst was used as the working electrode. 60 ml of 0.1 M KHCO3 solution was placed in the electrolytic cell. Before the test, CO2 was continuously injected into the electrolyte at a rate of 20 ml / min for at least half an hour until saturation. Then, CO2 was reduced at a constant potential under continuous CO2 supply. Electrolysis was carried out at different constant potentials, and the composition of the products at each specific potential was determined.

[0038] The potential control during the constant potential reduction process is -1.3V to -1.8V. When preparing the working electrode, 5mg of catalyst is dispersed in 980μL of anhydrous ethanol, and then 20μL of Nafion 117 solution is added. The mixture is sonicated for 40min to form a uniform ink. 200μL of the ink is then dropped onto carbon paper and dried under an infrared lamp for use.

[0039] Preferably, the Ni-NC particles are calcined in an air atmosphere at 250-350°C for 0 hours, i.e., they are not calcined.

[0040] Preferably, the Ni-NC particles are calcined in an air atmosphere at 250–350°C for 1 hour.

[0041] Preferably, the Ni-NC particles are calcined in an air atmosphere at 250–350°C for 3 hours.

[0042] Preferably, the Ni-NC particles are calcined in an air atmosphere at 250–350°C for 6 hours.

[0043] Preferably, the Ni-NC particles are calcined in an air atmosphere at 250–350°C for 9 hours.

[0044] Preferably, the Ni-NC particles are calcined in an air atmosphere at 250–350°C for 12 hours.

[0045] Applications of Ni-NC materials include systems that regulate the change in syngas ratio as the Ni-NC oxidation time increases.

[0046] Example 1:

[0047] Step 1: First, prepare the Ni-NC precursor solution. Add 3.5 mmol of ZnCl2 powder and 0.1 mmol of Ni(NO3)2 solid to 30 ml of formamide solution and stir to dissolve. Transfer the solution to a 50 ml Teflon-lined stainless steel autoclave and seal immediately. Keep it in an oven at 180°C for 12 hours. After naturally cooling to room temperature, wash the resulting solution several times with deionized water and anhydrous ethanol, filter, and dry at 60°C overnight to obtain a black solid.

[0048] Step 2: Next, the black solid was calcined in an argon atmosphere at 850–950°C for 2 hours to obtain Ni-NC particles. Without oxidation treatment, the previously treated Ni-NC particles were calcined in an air atmosphere at 250–350°C for 0 hours.

[0049] Step 3: In an H-type electrolytic cell divided into an anode and cathode compartment by a Nafion 117 proton exchange membrane (PEM), a platinum sheet and Ag / AgCl (3.5M saturated KCl solution) were used as the counter electrode and reference electrode, respectively, at a depth of 1.0 × 1.0 cm. 2 Carbon paper coated with a catalyst is used as the working electrode.

[0050] To prepare the working electrode, 5 mg of catalyst was dispersed in 980 μL of anhydrous ethanol, and then 20 μL of Nafion 117 solution was added. The mixture was sonicated for 40 min to form a uniform ink. 200 μL of the ink was then dropped onto carbon paper and dried under an infrared lamp before use.

[0051] 60 ml of 0.1 M KHCO3 solution was added to the electrolytic cell. Before testing, CO2 or Ar was continuously injected into the electrolyte at a rate of 20 ml / min for at least half an hour until saturation. Then, CO2 was reduced at a constant potential under continuous CO2 flow. Electrolysis was carried out at different constant potentials, with the potential controlled between -1.3 V and -1.8 V during the constant potential reduction process. After electrolysis stabilized, the Faraday efficiency of CO was observed to be approximately 90%, and the Faraday efficiency of H2 was approximately 10%.

[0052] Example 2:

[0053] Step 1: First, prepare the Ni-NC precursor solution. Add 3.5 mmol of ZnCl2 powder and 0.1 mmol of Ni(NO3)2 solid to 30 ml of formamide solution and stir to dissolve. Transfer the solution to a 50 ml Teflon-lined stainless steel autoclave and seal immediately. Keep it in an oven at 180°C for 12 hours. After naturally cooling to room temperature, wash the resulting solution several times with deionized water and anhydrous ethanol, filter, and dry at 60°C overnight to obtain a black solid.

[0054] Step 2: Next, the black solid was calcined in an argon atmosphere at 850–950°C for 2 hours to obtain Ni-NC particles. Then, the previously treated Ni-NC particles were calcined in an air atmosphere at 250–350°C for 1 hour.

[0055] Step 3: In an H-type electrolytic cell divided into an anode and cathode compartment by a Nafion 117 proton exchange membrane (PEM), a platinum sheet and Ag / AgCl (3.5M saturated KCl solution) were used as the counter electrode and reference electrode, respectively, at a depth of 1.0 × 1.0 cm. 2 A catalyst-coated carbon paper was used as the working electrode. To prepare the working electrode, 5 mg of catalyst was dispersed in 980 μL of anhydrous ethanol, followed by the addition of 20 μL of Nafion 117 solution. The mixture was sonicated for 40 min to form a uniform ink. 200 μL of this ink was then dropped onto the carbon paper and dried under an infrared lamp before use. The electrolytic cell contained 60 ml of 0.1 M KHCO3 solution. Before testing, CO2 or Ar was continuously injected into the electrolyte at a rate of 20 ml / min for at least half an hour until saturation. Then, CO2 was reduced at a constant potential under continuous CO2 flow. Electrolysis was performed at different constant potentials, with the potential controlled between -1.3 V and -1.8 V during the constant potential reduction process. After electrolysis stabilized, the Faraday efficiency of CO was observed to be approximately 70%, and the Faraday efficiency of H2 was approximately 30%.

[0056] Example 3:

[0057] Step 1: First, prepare the Ni-NC precursor solution. Add 3.5 mmol of ZnCl2 powder and 0.1 mmol of Ni(NO3)2 solid to 30 ml of formamide solution and stir to dissolve. Transfer the solution to a 50 ml Teflon-lined stainless steel autoclave and seal immediately. Keep it in an oven at 180°C for 12 hours. After naturally cooling to room temperature, wash the resulting solution several times with deionized water and anhydrous ethanol, filter, and dry at 60°C overnight to obtain a black solid.

[0058] Step 2: Next, the black solid was calcined in an argon atmosphere at 850–950°C for 2 hours to obtain Ni-NC particles. Then, the previously treated Ni-NC particles were calcined in an air atmosphere at 250–350°C for 3 hours.

[0059] Step 3: In an H-type electrolytic cell divided into an anode and cathode compartment by a Nafion 117 proton exchange membrane (PEM), a platinum sheet and Ag / AgCl (3.5M saturated KCl solution) were used as the counter electrode and reference electrode, respectively, at a depth of 1.0 × 1.0 cm. 2A catalyst-coated carbon paper was used as the working electrode. To prepare the working electrode, 5 mg of catalyst was dispersed in 980 μL of anhydrous ethanol, followed by the addition of 20 μL of Nafion 117 solution. The mixture was sonicated for 40 min to form a uniform ink. 200 μL of this ink was then dropped onto the carbon paper and dried under an infrared lamp before use. The electrolytic cell contained 60 ml of 0.1 M KHCO3 solution. Before testing, CO2 or Ar was continuously injected into the electrolyte at a rate of 20 ml / min for at least half an hour until saturation. Then, CO2 was reduced at a constant potential under continuous CO2 flow. Electrolysis was performed at different constant potentials, with the potential controlled between -1.3 V and -1.8 V during the constant potential reduction process. After electrolysis stabilized, the Faraday efficiency of CO was observed to be approximately 55%, and that of H2 approximately 45%.

[0060] Example 4:

[0061] Step 1: First, prepare the Ni-NC precursor solution. Add 3.5 mmol of ZnCl2 powder and 0.1 mmol of Ni(NO3)2 solid to 30 ml of formamide solution and stir to dissolve. Transfer the solution to a 50 ml Teflon-lined stainless steel autoclave and seal immediately. Keep it in an oven at 180°C for 12 hours. After naturally cooling to room temperature, wash the resulting solution several times with deionized water and anhydrous ethanol, filter, and dry at 60°C overnight to obtain a black solid.

[0062] Step 2: Next, the black solid was calcined in an argon atmosphere at 850–950°C for 2 hours to obtain Ni-NC particles. Then, the previously treated Ni-NC particles were calcined in an air atmosphere at 250–350°C for 6 hours.

[0063] Step 3: In an H-type electrolytic cell divided into an anode and cathode compartment by a Nafion 117 proton exchange membrane (PEM), a platinum sheet and Ag / AgCl (3.5M saturated KCl solution) were used as the counter electrode and reference electrode, respectively, at a depth of 1.0 × 1.0 cm. 2 A catalyst-coated carbon paper was used as the working electrode. To prepare the working electrode, 5 mg of catalyst was dispersed in 980 μL of anhydrous ethanol, followed by the addition of 20 μL of Nafion 117 solution. The mixture was sonicated for 40 min to form a uniform ink. 200 μL of this ink was then dropped onto the carbon paper and dried under an infrared lamp before use. The electrolytic cell contained 60 ml of 0.1 M KHCO3 solution. Before testing, CO2 or Ar was continuously injected into the electrolyte at a rate of 20 ml / min for at least half an hour until saturation. Then, CO2 was reduced at a constant potential under continuous CO2 flow. Electrolysis was performed at different constant potentials, with the potential controlled between -1.3 V and -1.8 V during the constant potential reduction process. After electrolysis stabilized, the Faraday efficiency of CO was observed to be approximately 35%, and the Faraday efficiency of H2 was approximately 65%.

[0064] Example 5:

[0065] Step 1: First, prepare the Ni-NC precursor solution. Add 3.5 mmol of ZnCl2 powder and 0.1 mmol of Ni(NO3)2 solid to 30 ml of formamide solution and stir to dissolve. Transfer the solution to a 50 ml Teflon-lined stainless steel autoclave and seal immediately. Keep it in an oven at 180°C for 12 hours. After naturally cooling to room temperature, wash the resulting solution several times with deionized water and anhydrous ethanol, filter, and dry at 60°C overnight to obtain a black solid.

[0066] Step 2: Next, the black solid was calcined in an argon atmosphere at 850–950°C for 2 hours to obtain Ni-NC particles. Then, the previously treated Ni-NC particles were calcined in an air atmosphere at 250–350°C for 9 hours.

[0067] Step 3: In an H-type electrolytic cell divided into an anode and cathode compartment by a Nafion 117 proton exchange membrane (PEM), a platinum sheet and Ag / AgCl (3.5M saturated KCl solution) were used as the counter electrode and reference electrode, respectively, at a depth of 1.0 × 1.0 cm. 2 A catalyst-coated carbon paper was used as the working electrode. To prepare the working electrode, 5 mg of catalyst was dispersed in 980 μL of anhydrous ethanol, followed by the addition of 20 μL of Nafion 117 solution. The mixture was sonicated for 40 min to form a uniform ink. 200 μL of this ink was then dropped onto the carbon paper and dried under an infrared lamp before use. The electrolytic cell contained 60 ml of 0.1 M KHCO3 solution. Before testing, CO2 or Ar was continuously injected into the electrolyte at a rate of 20 ml / min for at least half an hour until saturation. Then, CO2 was reduced at a constant potential under continuous CO2 flow. Electrolysis was performed at different constant potentials, with the potential controlled between -1.3 V and -1.8 V during the constant potential reduction process. After electrolysis stabilized, the Faraday efficiency of CO was observed to be approximately 25%, and the Faraday efficiency of H2 was approximately 75%.

[0068] Example 6:

[0069] Step 1: First, prepare the Ni-NC precursor solution. Add 3.5 mmol of ZnCl2 powder and 0.1 mmol of Ni(NO3)2 solid to 30 ml of formamide solution and stir to dissolve. Transfer the solution to a 50 ml Teflon-lined stainless steel autoclave and seal immediately. Keep it in an oven at 180°C for 12 hours. After naturally cooling to room temperature, wash the resulting solution several times with deionized water and anhydrous ethanol, filter, and dry at 60°C overnight to obtain a black solid.

[0070] Step 2: Next, the black solid was calcined in an argon atmosphere at 850–950°C for 2 hours to obtain Ni-NC particles. Then, the previously treated Ni-NC particles were calcined in an air atmosphere at 250–350°C for 12 hours.

[0071] Step 3: In an H-type electrolytic cell divided into an anode and cathode compartment by a Nafion 117 proton exchange membrane (PEM), a platinum sheet and Ag / AgCl (3.5M saturated KCl solution) were used as the counter electrode and reference electrode, respectively, at a depth of 1.0 × 1.0 cm. 2 A catalyst-coated carbon paper was used as the working electrode. To prepare the working electrode, 5 mg of catalyst was dispersed in 980 μL of anhydrous ethanol, followed by the addition of 20 μL of Nafion 117 solution. The mixture was sonicated for 40 min to form a uniform ink. 200 μL of this ink was then dropped onto the carbon paper and dried under an infrared lamp before use. The electrolytic cell contained 60 ml of 0.1 M KHCO3 solution. Before testing, CO2 or Ar was continuously injected into the electrolyte at a rate of 20 ml / min for at least half an hour until saturation. Then, CO2 was reduced at a constant potential under continuous CO2 flow. Electrolysis was performed at different constant potentials, with the potential controlled between -1.3 V and -1.8 V during the constant potential reduction process. After electrolysis stabilized, the Faraday efficiency of CO was observed to be approximately 25%, and the Faraday efficiency of H2 was approximately 75%.

[0072] Figure 1 The X-ray diffraction analysis results of the Ni-NC catalyst at different oxidation times of the present invention are shown. The chemical environment of Ni, O and C in the catalyst is analyzed by XRD.

[0073] Figure 2 The following are scanning electron microscope analysis results of the surface of Ni-NC catalyst at different oxidation times (0h, 1h, 3h, 6h, 9h, 12h) according to the present invention, which can observe the morphology of the catalyst at different oxidation times.

[0074] Figure 3 The present invention is Ni-NC@Ni NCs Aberration-corrected electron microscopy analysis of the (3h) surface revealed the formation of nickel nanoclusters.

[0075] Figure 4 The linear sweep voltammetry (LSV) tests were performed on six samples of Ni-NC catalyst oxidized for different times in this invention.

[0076] Figure 5This diagram shows the Faraday efficiency of the Ni-NC catalyst after different oxidation times at different potentials for CO2 reduction to CO. It can be seen that within the range of -1.3 to -1.8 V, the proportion of CO gradually decreases while the proportion of H2 gradually increases. Quantitative analysis of CO and H2 products was performed using gas chromatography with a flame atomization detector (FID) and high-purity nitrogen as the carrier gas.

[0077] Figure 6 This is a graph showing the change in current density over time during the electrocatalytic reduction of CO2 to CO by the Ni-NC catalyst after 3 hours of oxidation, at a constant potential of -1.6V. It can be seen that the catalyst can stably react for 20 hours at this potential.

[0078] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A controllable synthesis method for Ni-NC materials, characterized in that, Includes the following steps: Step 1: Prepare the solution and synthesize the black solid; First, prepare the Ni-NC precursor solution by adding 3.5 mmol of ZnCl2 powder and 0.1 mmol of Ni(NO3)2 solid to 30 ml of formamide solution and stirring to dissolve. Transfer the solution to a 50 ml Teflon-lined stainless steel autoclave and seal it immediately. Keep it in an oven at 180 °C for 12 hours. After naturally cooling to room temperature, wash the obtained solution several times with deionized water and anhydrous ethanol, filter it, and dry it at 60 °C overnight to obtain a black solid. Step 2: Preparation of Ni-NC catalyst; Ni-NC particles were obtained by calcining a black solid in an argon atmosphere at 850-950 °C for 2 h; the previously treated Ni-NC particles were then calcined in an air atmosphere at 250-350 °C, and the ratio of Ni-NC to nickel nanoclusters was controlled to prepare a catalyst. Step 3: Prepare the working electrode; In an H-type electrolytic cell divided into an anode and cathode compartment by a Nafion 117 proton exchange membrane, a platinum sheet and Ag / AgCl were used as the counter electrode and reference electrode, respectively. (1.0 × 1.0 cm) 2 Carbon paper coated with a catalyst was used as the working electrode. 60 ml of 0.1 M KHCO3 solution was placed in the electrolytic cell. Before the test, CO2 was continuously injected into the electrolyte at a rate of 20 ml / min for at least half an hour until saturation. Then, CO2 was reduced at a constant potential under the condition of continuous CO2 introduction. The potential control during the constant potential reduction process is -1.3 V to -1.8 V. When preparing the working electrode, 5 mg of catalyst is dispersed in 980 μL of anhydrous ethanol, and then 20 μL of Nafion 117 solution is added. The mixture is sonicated for 40 min to form a uniform ink. 200 μL of the ink is then dropped onto carbon paper and dried under an infrared lamp for use.

2. The controllable synthesis method of Ni-NC material according to claim 1, characterized in that, The Ni-NC particles were calcined in air at 250 ~ 350 °C for 1 hour.

3. The controllable synthesis method of Ni-NC material according to claim 1, characterized in that, The Ni-NC particles were calcined in air at 250 ~ 350 °C for 3 hours.

4. The controllable synthesis method of Ni-NC material according to claim 1, characterized in that, The Ni-NC particles were calcined in air at 250 ~ 350 °C for 6 hours.

5. The controllable synthesis method of Ni-NC material according to claim 1, characterized in that, The Ni-NC particles were calcined in an air atmosphere at 250 ~ 350 °C for 9 hours.

6. The controllable synthesis method of Ni-NC material according to claim 1, characterized in that, The Ni-NC particles were calcined in an air atmosphere at 250 ~ 350 °C for 12 hours.

7. The application of Ni-NC materials obtained by the controllable synthesis method according to any one of claims 1-6, characterized in that, Used for electrolytic reduction of CO2 into a mixture of CO and H2.

Citation Information

Patent Citations

  • Ni monatomic catalyst for electrocatalytic CO2 reduction and preparation method and application thereof

    CN116516390A